2016
DOI: 10.1111/apv.12130
|View full text |Cite
|
Sign up to set email alerts
|

Food localism and resistance: a revival of agriculture and cross‐border relations in Hong Kong

Abstract: Hong Kong, a part of China, yet separated from it by a borderline and a different social system, relies mostly on China for its fresh food. With a high incidence of food contamination, many Hong Kong people have turned to a new food alternative – locally grown organic vegetables. The number of organic growers has risen significantly over the past decade. This paper examines the emergence of local organic food production in Hong Kong since the turn of the century. Not only is this revival of an interest in agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Strong promotion of local food consumption will also multiply economic transactions between conscientious consumers and local food producers at the rural farms. Chan (2016, p. 314) uses the term “food localism” to “demarcate the public discourse that stresses an awareness of locally and ecologically produced food, which signified better food quality”, and the trends include eating local food, supporting local small-holding farmers and developing community-supported agriculture to grow food ecologically. This trend in consuming local food results in lower food miles and reduced carbon footprint, a positive environmental impact of agritourism (Shah et al , 2019).…”
Section: Literature Review: Agritourism and The Local Food Systemmentioning
confidence: 99%
“…Strong promotion of local food consumption will also multiply economic transactions between conscientious consumers and local food producers at the rural farms. Chan (2016, p. 314) uses the term “food localism” to “demarcate the public discourse that stresses an awareness of locally and ecologically produced food, which signified better food quality”, and the trends include eating local food, supporting local small-holding farmers and developing community-supported agriculture to grow food ecologically. This trend in consuming local food results in lower food miles and reduced carbon footprint, a positive environmental impact of agritourism (Shah et al , 2019).…”
Section: Literature Review: Agritourism and The Local Food Systemmentioning
confidence: 99%
“…The relationship between FTT activities and environmental sustainability in relation to food is mediated through the production and farming of locally sourced and grown food materials. Chan (2016) uses the term "food localism" to "demarcate the public discourse that stresses an awareness of locally and ecologically produced food, which signified better food quality" and the trends include, "eating local food, supporting local small-holding farmers and developing community-supported agriculture to grow food ecologically" (2016, pp. 313-314).…”
Section: Farm-to-table and Sustainable Developmentmentioning
confidence: 99%
“…Food scares as a result of China's expanding exports have generated a variety of reactions among Asian countries beyond traditional consumerism. Chan's (2016) sophisticated ethnographic research on local food production in Hong Kong revealed how local organic food production in Hong Kong is a form of "food resistance" against unsafe food products from China. This type of resistance coincides with the general resistance against the encroachment of mainland China's political directives in post-1997 Hong Kong.…”
Section: Borders As Assemblagesmentioning
confidence: 99%